An estimate of Solar Radiation over India in the pre-monsoon season - GUPTA, M. G. (MAUSAM, 1966)
The computations of diabatic heating over India in the pre-monsoon season, with the help of a simple formula due to Mintz (1958), indicate the gradual build up of a zone of diabatic heating over central India from March to May. These results have been checked against estimates of net radiation over India during March, April and May. For this purpose the outgoing long wave radiation was computed with the help of Elsasser's radiation diagram, the results of which agree fairly well with the measurements of long wave radiation by Tiros IV. For incoming solar radiation, mean values based on 2-6 years' data of pyrheliometer observations have been utilised. By subtracting the outgoing radiation from the sum of (a) the radiation observed at the surface of the earth and (b) the radiation absorbed by the atmosphere, an estimate of the net radiation for diabatic heating has been obtained. The value thus obtained, are generally higher than the value given by Mintz's formula. But there is fairly good agreement on the order of magnitude.